2020
DOI: 10.1039/c9py01035a
|View full text |Cite
|
Sign up to set email alerts
|

Non-solvating, side-chain polymer electrolytes as lithium single-ion conductors: synthesis and ion transport characterization

Abstract: Non-solvating, side-chain polymer electrolytes with more dissociable pendent anion chemistries exhibit a dielectric relaxation dominated lithium ion transport mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 44 publications
3
78
1
Order By: Relevance
“…[ 10 ] For low Li‐salt doping contents, the dense electrostatic attractions within LiPSTFSI and the (dynamic) crosslinking, renders the matrix very rigid and an Arrhenius behavior. [ 33 ] For higher doping contents, there is a delicate balance between increased permittivity which affects redissociation of ion pairs and the formation of triplets and higher aggregates, and the overall decrease in ion mobility. [ 34 ] At this stage, the clusters and agglomerates can arguably be arranged in such a way that continuous Li + conduction pathways are created, percolation threshold is reached, impacting positively the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] For low Li‐salt doping contents, the dense electrostatic attractions within LiPSTFSI and the (dynamic) crosslinking, renders the matrix very rigid and an Arrhenius behavior. [ 33 ] For higher doping contents, there is a delicate balance between increased permittivity which affects redissociation of ion pairs and the formation of triplets and higher aggregates, and the overall decrease in ion mobility. [ 34 ] At this stage, the clusters and agglomerates can arguably be arranged in such a way that continuous Li + conduction pathways are created, percolation threshold is reached, impacting positively the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…This is also reflected in the hightemperature ionic conductivity data-where the added temperature eases the polymer chain dynamics even more and 50-60 wt% creates a maximum (Figure 8), which has been observed previously for other concentrated systems. [23,25] There is no simple rule as to what ion conduction mechanism is to be preferred or the ideal to achieve the higher ionic conductivities, but recent studies have demonstrated the possibility of decoupling the conductivity from the mechanical motions typically at temperatures approaching the T g , either by creating systems with low T g s and high contents of aggregated ionic domains, [35,38,39] or as Liu et al [33] engineer the local environment by placing different anion groups on the side chains of LiPSTFSI. Indeed, for PS-based SICs/SPEs ion transport occur even when the polymer segmental motions are slow.…”
Section: Ion Transport and Conduction Mechanism(s) Analysismentioning
confidence: 99%
“…Here, the curve in the high-frequency region is related to the dielectric relaxation process and the slope at mid-lowfrequency region is related to the electrode polarization (EP) process. Then, the dielectric relaxation time was extracted via fitting ε der ′ ′ to the Havriliak-Negami (HN) equation, which gives the HN relaxation time (τ HN ) [38,39]:…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of the three decane-tailed materials follows the trend of higher conductivity with lower ionpair binding energy, the same as with our previous findings for a polymer system. 42 In Figure 7, conductivity curves of LiC10TFSI and LiC18TFSI are compared to better understand the effect of the material phase. The faster dynamics of these two molecules not only affected their phase change kinetics but also improved conductivity.…”
Section: Ionic Conductivitymentioning
confidence: 99%